Impact Academic Pressure and Academic Ability Against Academic Cheating - Miranda, Cindy Ara; Uyun, Muhamad (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Education is a means of educating the nation's children who are knowledgeable and noble. However, many students are found who do not reflect noble morals. one of the behaviors that do not reflect noble morals is academic cheating. Academic fraud is dishonest behavior by students in learning. The causes of academic cheating include academic pressure and academic ability. Great academic pressure and academic ability make students commit academic fraud. This study aims to prove the correlation between academic pressure and academic ability to academic fraud committed by students. The research subjects were active students of the Faculty of Psychology. Type of correlational quantitative research with a scale as a Likert model research instrument. Sampling using purposive random sampling of as many as 191 subjects. Data were collected using measuring instruments in the form of an academic pressure scale, academic ability scale, and academic cheating scale in the form of Google Forms. Data analysis using multiple regression. The results of the data analysis showed that academic pressure and academic ability impact on of academic fraud with a significant value of p = 0.000 (0.000 < 0.005). Academic pressure and academic ability impact academic fraud by 35.3%, and the remaining 64.7% is influenced by other factors. The results showed that the greater the academic pressure and academic ability in students, the greater the academic fraud that occurs.Pendidikan merupakan serana mencerdaskan anak bangsa yang berilmu dan berakhlak mulia. Namun faktanya banyak ditemukan peserta didik yang tidak mencerminkan akhlak mulia. Salah satu perilaku yang tidak mencerminkan akhlak mulia adalah melakukan kecurangan akademik. Kecurangan akademik merupakan perilaku tidak jujur yang dilakukan peserta didik dalam pembelajaran. Penyebab kecurangan akademik diantaranya tekanan akademik dan kemampuan akademik. Tekanan akademik dan kemampuan akademik yang besar membuat peserta didik melakukan kecurangan akademik. Penelitian ini bertujuan untuk membuktikan korelasi tekanan akademik dan kemampuan akademik terhadap kecurangan akademik yang dilakukan oleh mahasiswa. Subjek penelitian mahasiswa aktif Fakultas Psikologi. Jenis penelitian kuantitatif korelasional dengan skala sebagai instrumen penelitian model likert. Pengambilan sampel menggunakan purposive random sampling sebanyak 191 subjek. Data dikumpulkan menggunakan alat ukur berupa skala tekanan akademik, skala kemampuan akademik dan skala kecurangan akademik dalam bentuk google form. Analisis data menggunakan regresi ganda. Hasil analisis data menunjukkan bahwa tekanan akademik dan kemampuan akademik berdampak pada kecurangan akademik dengan nilai signifikan p=0,000 (0,000 < 0,005). Tekanan akademik dan kemampuan akademik memiliki dampak terhadap kecurangan akademik sebesar 35,3 %, sisanya 64,7 % dipengaruhi oleh faktor lain. Hasil penelitian menunjukkan bahwa jika semakin besar tekanan akademik dan kemampuan akademik pada mahasiswa, maka semakin besar pula kecurangan akademik yang terjadi.